Peningkatan Kompetensi Guru melalui Pelatihan Pembuatan Media Ajar Berbasis Digital di SMP Negeri 6 Tinggimoncong Kabupaten Gowa - Hatta, A. Afrinaramadhani; Rahmat, Irwandi; Alqadri, Zulqifli; Fatkhulloh, Shoffan; Tawil, Muh. (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2025)
This Community Service activity aims to enhance the competencies of teachers at SMP Negeri 6 Tinggimoncong through training in the development of digital teaching media. The training focuses on two main aspects: increasing knowledge about the types of digital teaching media that can be applied in teaching and improving teachers' skills in using Canva to design more creative teaching materials. The results of the training show a significant improvement in both aspects. Teachers' knowledge of digital teaching media increased from 30% to 80%, while their skills in using Canva increased from 25% to 75%. This improvement indicates that the training successfully broadened teachers' understanding of the use of technology in teaching and provided them with practical skills in designing engaging and effective teaching materials. With these new skills, teachers can enhance the quality of classroom instruction and create more interactive learning experiences for students. This training is also expected to offer solutions to the challenges faced by teachers in remote areas with limited access to technology and educational training.